2011
DOI: 10.1371/journal.pone.0017585
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Yersinia pestis into the Viable but Nonculturable State in a Low-Temperature Tap Water Microcosm

Abstract: Yersinia pestis, the causative agent of plague, has caused several pandemics throughout history and remains endemic in the rodent populations of the western United States. More recently, Y. pestis is one of several bacterial pathogens considered to be a potential agent of bioterrorism. Thus, elucidating potential mechanisms of survival and persistence in the environment would be important in the event of an intentional release of the organism. One such mechanism is entry into the viable but non-culturable (VBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 34 publications
3
47
0
Order By: Relevance
“…Also, the step of having a 7 day starvation before the stimulation could induce VBNC cells because they have intact cell membranes, low metabolic activity and continued mRNA synthesis (Lleo et al ., 2000). It has been known that many species of bacteria enter VBNC state when they are subjected to various environmental stressors, such as UV disinfection, osmotic pressures, high/low temperature and starvation (Colwell et al ., 1985; Byrd et al ., 1991; Oliver et al ., 2005; Pawlowski et al ., 2011). Interestingly, it has been demonstrated that VBNC and persister cells coexist after antibiotic treatment and can be resuscitated back to culturable cells when the existing stress is removed (Ayrapetyan et al ., 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the step of having a 7 day starvation before the stimulation could induce VBNC cells because they have intact cell membranes, low metabolic activity and continued mRNA synthesis (Lleo et al ., 2000). It has been known that many species of bacteria enter VBNC state when they are subjected to various environmental stressors, such as UV disinfection, osmotic pressures, high/low temperature and starvation (Colwell et al ., 1985; Byrd et al ., 1991; Oliver et al ., 2005; Pawlowski et al ., 2011). Interestingly, it has been demonstrated that VBNC and persister cells coexist after antibiotic treatment and can be resuscitated back to culturable cells when the existing stress is removed (Ayrapetyan et al ., 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…35 S-labelled methionine, 3 H-labelled leucine and 35 S-labelled cysteine/methionine have been used to detect viable cells in Shigella dysenteriae , E. faecalis and Y. pestis , respectively (Rahman et al, 1994; Lleò et al, 1998; Pawlowski et al, 2011). …”
Section: Detection Of Vbnc Cellsmentioning
confidence: 99%
“…These include confirmation of cellular membrane integrity, uptake of labeled amino acids, and protection of genomic DNA (5). For V .…”
Section: Are Vbnc Cells Living and Virulent?mentioning
confidence: 99%
“…Several factors such as antibiotic pressure, high/low temperature, starvation, chlorination, change in the pH, and oxygen stress can induce VBNC state of any bacteria (5, 35, 40). The culture supernatant of ameba Hartmannella vermiformis was shown to induce the VBNC state of Legionella pneumophila (41).…”
Section: Resuscitation Of Vbnc Bacteriamentioning
confidence: 99%